The magnetic field of the plasma tail of Comet 1P/Halley - Sizonenko, Yu.V. (Кинематика и физика небесных тел, 2005)
The photometric scans of the plasma tail of Comet Halley from four observation series are compared with the profiles of brightness distribution along the tail streams which were calculated on the basis of the diffusion model of the plasma tail. The magnetic field induction and the lifetime of ions in the tail of Comet Halley as well as the coefficients of diffusion are estimated. A probable connection between cometary magnetic field changes and cometary tail structure ones are discussed.